Consumer behavior of bread and its influence on "Supply Chain Management" an innovative approach - de Oliveira, Paulo Sergio Gonçalves; Araújo, Jeremias; Kaperaviczus, Alexandre Faro; da Silva, Luciano Ferreira; Bandero, Fabio Airton (Brazilian Journal of Operations & Production Management, 2020)
Purpose: The paper sought to describe factors contributing to the changes in the habits of consumers of processed bread since there was a tendency in the search for a whole-grain meal. Design/methodology/approach: Aiming to achieve the study objective, and a survey was used, with a sample of 155 consumers of processed bread through a questionnaire. The quality of the model was measured by the KMO test, which reached a value of 0.888, which is considered very good. Findings: The first solution presented a six-factor solution, which kept after Cronbach's Alpha analysis. The six factors named as product availability, nutritional quality, product development, information search, purchase decision based on product development, and willingness to pay. Originality: The originality of the research is because it analyzes the consumer behavior of processed food, to capture the changes that are taking place in the market, to use the supply chain, allowing manufacturers to meet demands faster, through the use of innovations created by an supply chain integration.